Evaluating the impact of allergic rhinitis on quality of life among Thai students. Issue 9 (21st April 2015) - Sapsaprang, Siwaporn; Setabutr, Dhave; Kulalert, Prapasri; Temboonnark, Panipak; Poachanukoon, Orapan
<x xml:space="preserve">Abstract</x> Background The prevalence of allergic rhinitis (AR) in Thailand continues to rise. We report the prevalence and evaluate its impact upon quality of life (QoL) in students on a metropolitan campus. Methods From March 2013 to February 2014, 222 students from Thammasat University Medical School were evaluated using the International Study of Asthma and Allergies in Childhood Questionnaire (ISAAC) questionnaire and the rhinoconjunctivitis QoL questionnaire (Rcq‐36) to assess subjective symptoms. Those students with clinical symptoms of AR underwent skin prick testing (SPT) using 5 common allergens found in Thailand. The association between AR and QoL was then determined using a paired t test. Results A total of 222 students were enrolled in the study; 86 (38.7%) were men. There were 183 (81.9%) students with AR symptoms and 130 (71.4%) students with positive results for SPT. The students' QoL as defined by the Rcq‐36 revealed a significant worsening in students who self‐reported rhinitis symptoms within the past 12 months. Compared to the non‐AR group, in those with AR, eye symptoms were significantly more common. Conclusion The prevalence of AR at a college campus was 58.5%. The presence of rhinitis symptoms was the highest predictor of the presence of AR, with 67.7% having subsequent positive SPT. Students with AR had poorer scores in every dimension of QoL as defined by the Rcq‐36 when compared to their non‐AR counterparts. Educational performances among the 2 groups were unaffected.